2021
DOI: 10.3389/fcell.2021.634512
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Non-coding RNAs and Insulin-Like Growth Factor Signaling in the Pathogenesis of Neoplasia

Abstract: The insulin-like growth factors (IGFs) are polypeptides with similar sequences with insulin. These factors regulate cell growth, development, maturation, and aging via different processes including the interplay with MAPK, Akt, and PI3K. IGF signaling participates in the pathogenesis of neoplasia, insulin resistance, diabetes mellitus, polycystic ovarian syndrome, cerebral ischemic injury, fatty liver disease, and several other conditions. Recent investigations have demonstrated the interplay between non-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 234 publications
1
6
0
Order By: Relevance
“…In vitro functional studies revealed that siRNA downregulating IGF-1R expression and podophyllin inhibiting IGF-1R phosphorylation downregulated the proliferation and migration potential of HCC cells and enhanced sorafenib-induced apoptosis (Figs. 2 , 3 and 4 ), which was consistent with published results [ 23 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In vitro functional studies revealed that siRNA downregulating IGF-1R expression and podophyllin inhibiting IGF-1R phosphorylation downregulated the proliferation and migration potential of HCC cells and enhanced sorafenib-induced apoptosis (Figs. 2 , 3 and 4 ), which was consistent with published results [ 23 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, silencing IGF-1R combined with sorafenib synergistically enhanced the apoptosis of HCC cells through the caspase / PARP pathway, suggesting that IGF-1R is involved in the proliferation, migration, and anti-apoptosis of HCC cells through the PI3K / Akt and Ras / Raf / ERK signaling pathways and negatively regulating the inhibitory effect of sorafenib on HCC. IGF-1R is overexpressed in lung cancer, breast cancer, pancreatic cancer, colorectal cancer, and HCC [23][24][25][26][27]. It is associated with tumor prognosis, and crosstalk between IGF-1R and PI3K/Akt and Ras/Raf/ERK signaling pathways is an important factor in the progression and drug resistance of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Aminopeptidase N is a transmembrane metalloprotease (CD13) overexpressed in human AML cells 24 . Insulin‐like growth factor‐1 , its receptor and binding proteins regulate cell growth important for survival of AML cells and are targets for therapy and biomarkers of AML and other malignant conditions 25–28 . Proteasome subunit alpha type‐5 is a member of a group of multi‐subunit proteases important for maintaining intracellular protein homeostasis during stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…24 Insulin-like growth factor-1, its receptor and binding proteins regulate cell growth important for survival of AML cells and are targets for therapy and biomarkers of AML and other malignant conditions. [25][26][27][28] Proteasome subunit alpha F I G U R E 4 Locally produced proteins in leukemic spleen lymph are downregulated in leukemic liver lymph and plasma. Log 2 -normalized mean intensities of the 29 proteins having lymph to plasma (L/P) abundance ratios >2 in leukemic spleen lymph (SL AML, n = 4) and L/P < 2 in control spleen lymph (SL Cntr, n = 4).…”
Section: Proteomic Pattern Of Known Amlrelated Proteinsmentioning
confidence: 99%
“…Unlike miRNAs, the molecular mechanisms of lncRNAs are complex ( Ernst et al, 2018 ; Ghafouri-Fard et al, 2021 ). Canonically, miRNAs are loaded into AGO2 to yield the RNA-induced silencing complex (RISC), which represses miRNAs’ targets expression ( Yuan et al, 2011 ; Quevillon Huberdeau and Simard, 2019 ).…”
Section: Introductionmentioning
confidence: 99%